Adaptive Sports Medicine A Clinical Guide (Springer International Publishing, 2018)
This first-of-its-kind text provides a comprehensive presentation and review of the unique aspects of adaptive sports medicine and adaptive athletes, who are increasingly active and prominent, not only individually and in local leagues and organizations but also in larger settings like the Paralympics. Divided into thematic sections, part one covers the history and natural course of the care, policies and laws that have been developed over the years for persons with disabilities, as well as the biomechanics and technology of wheelchair sports and adaptive sports prostheses. The medical considerations of the adaptive athlete comprise part two, including injury epidemiology, emergent care, and surgical and rehabilitative considerations. Part three, by far the most extensive section, discusses specific wheelchair and adaptive sports, including adaptive running, cycling, water sports and throwing sports, wheelchair basketball, softball and rugby, as well as adaptive combative and extreme sports. Selected topics, including event planning, advocacy and controversies such as doping, are covered in part four. A comprehensive yet practical text, Adaptive Sports Medicine is a go-to resource and will be an invaluable reference for any sports medicine or primary medicine practitioner working with this unique population.